The Effect of Academic Supervision and Principal Leadership Through Performance Motivation Toward The Teacher Performance - ahmadun, Ahmadun; Martono, S.; Prihatin, Titi (Educational Management, 2021)
Teachers’ performances that had not been maximum required more attention. Teachers’ performances were influenced by several factors, such as academic supervision, principal leadership, and performance motivation. Higher academic supervision, principal leadership, and teacher performance motivation would lead to better performance. This research aims to analyze the academic supervision and principal leadership through performance motivation as a mediator toward the Publics Islamic JHS teachers' performance in Demak Regency. The applied approach in this research was quantitative. The research population consisted of the teachers of Public Islamic JHS in Demak Regency. The sampling data technique was purposive sampling. The applied data analysis techniques were descriptive statistics and inferential statistics. The findings showed that academic supervision, principal leadership, and performance motivation were correlated directly to teachers’ performance. The academic supervision and principal leadership did not have a direct effect moderated by performance motivation toward teaches’ performance.